2017
DOI: 10.1101/225524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABAergic deficits and schizophrenia-like behaviors in a mouse model carrying patient-derived neuroligin-2 R215H mutation

Abstract: Schizophrenia (SCZ) is a chronic neuropsychiatric disorder caused by both genetic and environmental factors. It is featured by long-standing delusion and hallucination (psychosis), and cognitive deficits (Freedman, 2003; Insel, 2010; Lewis and Lieberman, 2000). SCZ is a highly heritable disorder (Sullivan et al., 2003) with a complex genetic basis. Recent genomic studies identified a number of genetic variants associated with . CC-BY 4.0 International license It is made available under a (which was not peer-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…In line with the molecular and cellular consequences of the R215H mutation in NLGN2, both KI mouse lines show behavioral pheno types that partially recapitulate the constitutive KO mice, including, most notably, the prominent increase in anxiety behaviors in the OF and EPM (93,97,98). They also display a far wider range of cognitive impairments than have previously been reported for the constitutive KO mice, including impaired spatial learning and memory in the Morris water maze and the novel location recogni tion test but not the novel object recognition test (97), as well as impairments in spontaneous alternation, contextual fear condition ing (93), and cued fear conditioning (98). Last, alterations in pre pulse inhibition and exaggerated stress responses after restraint stress were also reported (93,97), supporting the notion that these models recapitulate several core phenotypes of schizophrenia.…”
Section: Mouse Models Of Disease-associated Nlgn2 Variantsmentioning
confidence: 79%
See 4 more Smart Citations
“…In line with the molecular and cellular consequences of the R215H mutation in NLGN2, both KI mouse lines show behavioral pheno types that partially recapitulate the constitutive KO mice, including, most notably, the prominent increase in anxiety behaviors in the OF and EPM (93,97,98). They also display a far wider range of cognitive impairments than have previously been reported for the constitutive KO mice, including impaired spatial learning and memory in the Morris water maze and the novel location recogni tion test but not the novel object recognition test (97), as well as impairments in spontaneous alternation, contextual fear condition ing (93), and cued fear conditioning (98). Last, alterations in pre pulse inhibition and exaggerated stress responses after restraint stress were also reported (93,97), supporting the notion that these models recapitulate several core phenotypes of schizophrenia.…”
Section: Mouse Models Of Disease-associated Nlgn2 Variantsmentioning
confidence: 79%
“…Despite this residual expression, the Jiang et al line showed the expected impairment in inhibitory synapse function but not excitatory synapse function, with decreased levels of the postsynaptic GABArelated proteins gephyrin and GABA A R2 as well as reduced mIPSC frequency and amplitude in both the dentate gyrus of the hippocampus (93) and the mPFC (98). Notably and in discrepancy with the constitutive Nlgn2 KO mice, levels of the presynaptic markers PV and VIAAT were also found to be reduced in both brain regions (93,98), indicating that the resid ual NLGN2R215H mutant protein may confer a gain of function with respect to presynaptic development rather than mimicking loss of function, as has previously been reported for an autism related mutation in NLGN3 (11). Moreover, electrophysiological approaches revealed abnormal GABAergic network activity in the mPFC, with a specific reduction in the power of fast gamma oscilla tions at 60 to 100 Hz (98).…”
Section: Mouse Models Of Disease-associated Nlgn2 Variantsmentioning
confidence: 97%
See 3 more Smart Citations